ANALISA PENCAHAYAAN ALAMI BANGUNAN HUNIAN 2 LANTAI DI KOTA DEPOK - Dafa Sashi Ramdhani; Fadila Fitria Wulandari; Dimas Fa Adilah Ramdhani; Hendita Budi Pramana; Achmad Irfan Dwi Cahyono; Hartini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Natural lighting is an important aspect in building design that affects visual comfort and energy efficiency. In two-story residential houses located in urban areas, the distribution of natural lighting is often uneven due to factors such as building orientation, the position of openings, and the presence of obstructing elements. This study aims to analyze the intensity of natural lighting in a two-story residential house in Depok City and to evaluate its compliance with the Indonesian National Standard (SNI) 03-6197-2000.The research method used is a quantitative method with a descriptive approach through direct measurement using a lux meter. Measurements were conducted at three different times, namely at 08:00, 12:00, and 15:00 WIB in various rooms on the first and second floors. The collected data were analyzed comparatively by comparing the measurement results with the SNI standard.The results show that the overall level of natural lighting in the building does not meet the standard. On the first floor, only about 16.7%–33.3% of the rooms meet the standard, with an average illumination intensity ranging from 68 to 127.5 lux. Meanwhile, on the second floor, the lighting performance is better, with up to 80% of the rooms meeting the standard during midday, and an average intensity reaching 174 lux. The second floor has approximately 36% higher lighting levels compared to the first floor.The conclusion of this study indicates that natural lighting in the building is not yet optimal, particularly on the first floor. Therefore, improvements in the placement and dimensions of openings, as well as light distribution, are necessary to achieve more even and standard-compliant natural lighting.